2012
DOI: 10.1260/1369-4332.15.6.997
|View full text |Cite
|
Sign up to set email alerts
|

Prestress-Force Estimation in PSC Girder Using Modal Parameters and System Identification

Abstract: In this paper, a vibration-based method to estimate prestress-forces in a prestressed concrete (PSC) girder by using vibration characteristics and system identification (SID) approaches is presented. Firstly, a prestress-force monitoring method is formulated to estimate the change in prestress forces by measuring the change in modal parameters of a PSC beam. Secondly, a multi-phase SID scheme is designed on the basis of eigenvalue sensitivity concept to identify a baseline model that represents the target stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…Recently the interest on variability of dynamic properties of bridges (i.e. natural frequency, mode shape, damping ratio) caused by environmental effects such as temperature, humidity, wind and other factors is increasing [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently the interest on variability of dynamic properties of bridges (i.e. natural frequency, mode shape, damping ratio) caused by environmental effects such as temperature, humidity, wind and other factors is increasing [22].…”
Section: Discussionmentioning
confidence: 99%
“…Those indications are unexpected from numerical modal analysis, which is described in the later part. It has been reported that these noisy peaks can be caused by power supply issue of SHM-H sensor board [13]. Further studies should be made to resolve the problem related to the performance of the SHM-H sensor board.…”
Section: ) Wireless Communication and Power Consumptionmentioning
confidence: 99%
“…For vibration monitoring, SHM-A, SHM-AS and SHM-H sensor boards were selected. The SHM-A and SHM-H sensor boards were developed for acceleration measurement by University of Illinois at Urbana-Champaign (UIUC) [7,13,14]. The SHM-AS sensor board was modified from SHM-A sensor board in order to measure PZT's dynamic strain signal [15].…”
Section: Vibration and Impedance Smart Sensorsmentioning
confidence: 99%
“…Two simple supports were modeled by steel rods between the girder and the rigid frame. As detailed in existing publications [21], the PSC girder model has the T-section reinforced in both longitudinal and transverse direction with 10 mm diameter reinforcing bars. As the prestressing tendon, a seven-wire monostrand with 15 diameter was embedded in a 25 mm diameter duct.…”
Section: Experiments On Psc Girdermentioning
confidence: 99%